Strategi Pelayanan Biro Haji dan Umrah dalam Meningkatkan Jumlah Konsumen di Shafira Tour dan Travel Cabang Jember - Ubaidillah, Muhammad Ifan (Fakultas Dakwah UIN KHAS Jember, 2023)
Service strategy entails a series of intangible activities occurring through interactions between customers, employees, or other elements provided by a company's service provider, aiming to address customer problems or needs. This study aims to comprehend the service strategy of Shafira Tour & Travel Branch in Jember to increase customer numbers and the challenges it faces. A descriptive qualitative approach was employed, utilizing data collection techniques such as interviews, observations, and documentation. Findings reveal the utilization of the